The Value of Happiness: Well-Being on A Global Scale - Nikolaevna Yudina, Tatiana; Vladimirovna Fomicheva, Tatyana; Vladimirovna Dolgorukova, Irina; Ivanovna Kataeva, Valentina; Mihajlovna Kryukova, Elena (International Journal of Engineering and Technology, 2018)
scope of the publication is to describe the value (relevance) of happiness using comparative analysis of sociological and statistical data through various methods. Consideration of socio-cultural values is associated primarily with the transformational processes activating in the modern Russia and other countries. A comparative analysis of demographic processes in other countries was conducted to compare them with the similar processes taking place in Russia. The secondary analysis of sociological data of the World Values Survey international crosscultural project as well as the analysis of design indexes of "happiness levels" from the World Happiness Report 2017, the International Happiness Index or the Happy Planet Index (HPI) 2016 were carried out, allowing us to compare the indexing results, track the transformation processes related to the dynamics of sociocultural values in many countries of the world, as well as in Russia. The document analysis techniques used were the traditional (primary) analysis of documents, as well as secondary comparative analysis. Specialized quantitative content-analytical methods were practically tested during the work on this project. Thus, a "triangular approach" was used to study the processes in the value consciousness.Â Â